Respuesta :

Simplifying
3.6y = 5.4 + 3.3y

Solving
3.6y = 5.4 + 3.3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3.3y' to each side of the equation.
3.6y + -3.3y = 5.4 + 3.3y + -3.3y

Combine like terms: 3.6y + -3.3y = 0.3y
0.3y = 5.4 + 3.3y + -3.3y

Combine like terms: 3.3y + -3.3y = 0.0
0.3y = 5.4 + 0.0
0.3y = 5.4

Divide each side by '0.3'.
y = 18

Simplifying
y = 18


2. 3/5(a+5)=-1/3a-4

We move all terms to the left:

3/5(a+5)-(-1/3a-4)=0


Domain of the equation: 5(a+5)!=0

a∈R



Domain of the equation: 3a-4)!=0

a∈R

get rid of parentheses

3/5(a+5)+1/3a+4=0

calculate fractions

9a/(15a^2+75a)+(5aa/(15a^2+75a)+4=0


3. Simplifying
-2(x + 3) = 3x + -9 + -5x

Reorder the terms:
-2(3 + x) = 3x + -9 + -5x
(3 * -2 + x * -2) = 3x + -9 + -5x
(-6 + -2x) = 3x + -9 + -5x

Reorder the terms:
-6 + -2x = -9 + 3x + -5x

Combine like terms: 3x + -5x = -2x
-6 + -2x = -9 + -2x

Add '2x' to each side of the equation.
-6 + -2x + 2x = -9 + -2x + 2x

Combine like terms: -2x + 2x = 0
-6 + 0 = -9 + -2x + 2x
-6 = -9 + -2x + 2x

Combine like terms: -2x + 2x = 0
-6 = -9 + 0
-6 = -9

Solving
-6 = -9 (No solution)

4. Simplifying
2(x + -1) + 6x = 4(2x + -1) + 2

Reorder the terms:
2(-1 + x) + 6x = 4(2x + -1) + 2
(-1 * 2 + x * 2) + 6x = 4(2x + -1) + 2
(-2 + 2x) + 6x = 4(2x + -1) + 2

Combine like terms: 2x + 6x = 8x
-2 + 8x = 4(2x + -1) + 2

Reorder the terms:
-2 + 8x = 4(-1 + 2x) + 2
-2 + 8x = (-1 * 4 + 2x * 4) + 2
-2 + 8x = (-4 + 8x) + 2

Reorder the terms:
-2 + 8x = -4 + 2 + 8x

Combine like terms: -4 + 2 = -2
-2 + 8x = -2 + 8x

Add '2' to each side of the equation.
-2 + 2 + 8x = -2 + 2 + 8x

Combine like terms: -2 + 2 = 0
0 + 8x = -2 + 2 + 8x
8x = -2 + 2 + 8x

Combine like terms: -2 + 2 = 0
8x = 0 + 8x
8x = 8x

Add '-8x' to each side of the equation.
8x + -8x = 8x + -8x

Combine like terms: 8x + -8x = 0
0 = 8x + -8x

Combine like terms: 8x + -8x = 0
0 = 0

Solving
0 = 0 (all real numbers)